2021
DOI: 10.1136/jitc-2021-002949
|View full text |Cite
|
Sign up to set email alerts
|

CTLA4promoter hypomethylation is a negative prognostic biomarker at initial diagnosis but predicts response and favorable outcome to anti-PD-1 based immunotherapy in clear cell renal cell carcinoma

Abstract: BackgroundIn metastatic clear cell renal cell carcinoma (ccRCC), different combination therapies, each including anti-PD-1 immune checkpoint blockade (ICB), are applied as first-line treatment. Robust predictive biomarkers for rational upfront therapy decisions are lacking, although they are urgently needed. Recently, we showed that CTLA4 promoter methylation predicts response to ICB in melanoma. Here, we aimed to investigate CTLA4 methylation in ccRCC and its utility to serve as a predictive biomarker for ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 34 publications
5
24
0
Order By: Relevance
“…Immunity_H had lower tumor purity and higher immune score than Immunity_L, indicating that immune cells exerted critical role in inhibiting tumor progression. These findings supported previous researches that the activation of immune-related responses can effectively control the progression of KIRC [ 28 , 29 ]. Additionally, Immunity_H had higher levels of HLA genes expression and immune cells infiltration than Immunity_L, indicating that Immunity_H had stronger immunogenicity.…”
Section: Discussionsupporting
confidence: 92%
“…Immunity_H had lower tumor purity and higher immune score than Immunity_L, indicating that immune cells exerted critical role in inhibiting tumor progression. These findings supported previous researches that the activation of immune-related responses can effectively control the progression of KIRC [ 28 , 29 ]. Additionally, Immunity_H had higher levels of HLA genes expression and immune cells infiltration than Immunity_L, indicating that Immunity_H had stronger immunogenicity.…”
Section: Discussionsupporting
confidence: 92%
“…In the past decade, numerous studies have shown the effectiveness of immune checkpoint therapeutics in tackling several malignancies, particularly carcinomas [13,14,38,[45][46][47][48] and melanomas [16,49,50]. Several recent studies are actively investigating the potential role of targeted immunotherapy in a wide range of sarcomas [51].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proved that tumors divided into different subtypes often have different immune microenvironments and respond differently to immunotherapy. For the subtypes of ccRCC, the increased infiltration of immune cells suggests that these tumors are immune "hot tumors", otherwise they are called "cold tumors" (Galon and Bruni, 2019;Klumper, et al, 2021). To distinguish cold and hot tumors in ccRCC, patients were regrouped into two clusters by R package "ConensusClusterPlus" based on the expression levels of the 8 TRGs involved in modeling (Figure 8A; Supplementary Table S6).…”
Section: Estimation Of Intratumoral Immune Cell Infiltrationmentioning
confidence: 99%
“…For example, anti-programmed cell death protein 1(PD1) combined with anti-cytotoxic T lymphocyte antigen 4 (CTLA4) has become the first-line treatment of metastatic renal cell carcinoma. Although new targeted and immune agents continue to emerge and improve the prognosis of some patients, these drugs are still not suitable for all patients (Linehan and Ricketts, 2019;Samstein, et al, 2019;Kim, et al, 2021;Klumper, et al, 2021;Wu, et al, 2021;Wu, et al, 2022). Antineoplastic drugs are less effective in immunosuppressive tumor microenvironment (TME) (Lai, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation